Nutrition Interventions in Rheumatoid Arthritis: The Potential Use of Plant-Based Diets. A Review - Alwarith, Jihad; Kahleova, Hana; Rembert, Emilie; Yonas, Willy; Dort, Sara; Calcagno, Manuel; Burgess, Nora; Crosby, Lee; Barnard, Neal D. (Frontiers in Nutrition, 2019)
Rheumatoid arthritis (RA), a chronic inflammatory autoimmune disease, affects roughly 1% of the world’s population. RA pathogenesis remains unclear, but genetic factors account for 50-60% of the risk while the remaining 40-50% might be linked to environmental, modifiable factors, such as infectious diseases, tobacco smoking, gut bacteria, and nutrition. Dietary triggers may play an inciting role in the autoimmune process and a compromised intestinal barrier may allow food components or microorganisms to enter the blood stream, triggering inflammation. In addition, excessive body weight may affect pharmacotherapy response and the likelihood disease remission, as well as the risk of disease mortality. Evidence suggests that changes in diet might play an important role in RA management and remission. Several studies have suggested improvement in RA symptoms with diets excluding animal products. Studies have shown that dietary fiber found in these plant-based foods can improve gut bacteria composition and increase bacterial diversity in RA patients, thus reducing their inflammation and joint pain. Although some of the trigger foods in RA patients are individualized, a vegan diet helps improve symptoms by eliminating many of these foods. Further research is needed to test the effectiveness of plant-based diets on joint pain, inflammation, and quality of life in patients with RA.